Particle aspect analysis of e×b drift instability in the presence of non-uniform electric field - Misra K.D.; Tiwari M.S. (My University, 2025)
A physical mechanism and the dynamical details of the drift wave instability have been studied by investigating the trajectories of the charge particles in the presence of ambient magnetic field and non-uniform electric field. The effect of finite gyro-radius corrections have also been accounted. The general dispersion relation for the electrostatic drift wave has been obtained. The expression for the growth rate have been derived from an energy balance approach. Our expression reduces to well known results under limiting conditions. The finite gyroradius correction due to inhomogeneous electric field is found to have a destabilising effect. The important geophysical situations for the existence of inhomogeneous electric field have been outlined and potential application of this result have been indicated. © 1977 IOP Publishing Ltd.